Review of Tourism Geography to Preservation of Barong Ider Bumi Cultures in Banyuwangi Regency Indonesia - Khakim, Mochammad Nurfahrul Lukmanul; Insani, Nailul; Anggraeni, Restia Minati; Lailah, Eka Tanti Nur (Graduate School, Universitas Brawijaya, 2020)
Kemiren Village, one of the cultural tourism villages in Banyuwangi, has a unique tradition that is usually held every year. This tradition is often referred to as Ider Bumi or Barong Ider. Barong Ider is the main attraction for tourism. The aims of this study are: (1) knowing the Kemiren Village as the village that owns the culture, (2) knowing the Barong Ider Bumi tradition, (3) knowing the development of Barong Ider Bumi as a tourist attraction based on a Geography Tourism perspective. The method of this research is qualitative descriptive. Research steps start from determining the issues, observation, library research, and interviews. Data analysis was done by using the Geography Tourism perspective. Kemiren cultural tourism village seeks to maintain the authenticity of their ancestral culture and traditions. With the authenticity and wisdom of their culture, it becomes the main attraction for tourists. Although many new cultures are coming in, their culture and traditions are still very awake. The Kemiren Village Community made various improvements in terms of public services for tourists without changing the authenticity of their culture. Tourism Geography Study explained that's the cultural tourism of Barong Ider Bumi, which has attracted tourists by providing tourist facilities properly. Barong Ider Bumi, as cultural tourism, produces various advancements and improvements in terms of economic and social life in Banyuwangi.Keywords: Barong Ider Bumi, cultural tourism, preservation ways.